Sub-Saharan African Eurobond yields: What really matters beyond global factors? - Christian Senga; Danny Cassimon; Dennis Essers (Review of Development Finance, 2018)
This study explores the drivers of secondary market yields of Sub-Saharan African (SSA) sovereign Eurobonds from 2008 to mid-2017. Our results indicate that, beyond global 'push' factors, country-specific 'pull' factors such as inflation and GDP growth matter too for SSA Eurobond performance. A panel error-correction analysis suggests large heterogeneity in the short-term influence of our global and country variables across countries. We find no significant effect of bond-specific factors on yields when push and pull factors are accounted for. By emphasizing the prominence of country variables, reflecting the quality of countries' macroeconomic management and their economic performance, our results qualify the common view that SSA countries have little control over their market borrowing costs.
Keywords: F34; G15; H63; 650; Public debt; International bonds; Bond yields; Sub-Saharan Africa